Peran Matemika Dalam Analisis Stabilitas Pengaspalan Pada Jalan Raya - Della Telaumbanua (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
Paving stability is the main indicator in determining the ability of flexible pavement to withstand repeated traffic loads and environmental influences during the design life of the road. This study aims to analyze the role of mathematical approaches in evaluating the stability of Asphalt Concrete–Binder Course (AC-BC) mixtures through Marshall tests and simple numerical modeling. The research method was carried out experimentally in the laboratory with variations in asphalt content of 5–7% and variations in soaking time of 30 minutes, 6 hours, and 9 hours. Asphalt content is a parameter that determines the stability and durability of flexible pavements on highways. Operational temperature is a dominant factor that influences the stability and resistance of flexible pavement to permanent deformation (rutting). The relationship between temperature and stability can be modeled mathematically with a high degree of correlation. The rutting prediction model developed is able to explain the tendency of pavement conditions in the field, thus indicating that a mathematical approach plays an important role in designing flexible pavements that are adaptive to tropical climate conditions. Water is also one of the environmental factors that most influence the decline in the quality of flexible pavement performance, especially in tropical climates with high rainfall that cause damage to flexible pavements such as decreased stability and permanent deformation (rutting) to become major problems on highways, which makes asphalt stability an essential parameter in the design and maintenance of flexible pavements, which is directly related to the ability of the pavement structure to withstand traffic loads and environmental conditions throughout the design period. Test data were analyzed using descriptive statistics, linear regression analysis, and correlation to identify quantitative relationships between mixture variables and stability and flow values. The results of the study indicate that the relationship between asphalt content and stability forms a parabolic curve pattern, where maximum stability is achieved at a certain asphalt content. Statistical analysis shows a strong negative correlation between soaking time and stability, indicating a decrease in the durability of the mixture due to the influence of water, which makes the study show that the mathematical model is able to describe the complex relationship between water factors, traffic loads, and structural responses of the pavement.